Proven strategies in competitive intelligence : lessons from the trenches - Prescott, John E.; Miller, Stephen H., 1956- (Wiley, 2001)
Tested-in-the-trenches competitive intelligence techniques used at today's top companies. This book brings together the best thinking and practices in competitive intelligence (CI) currently being used at many of today's most successful companies. Featuring contributions from leading industry executives, it covers CI strategies across a wide range of business functions, including marketing and sales, market research and forecasting, product development, and teams.